DESIGN REGULARITIES OF AN AUTOMATED PEDAGOGICAL DIAGNOSTICS SYSTEM (Journal of Information Technologies in Education (ITE), 2010)
Efficiency of designing of pedagogical diagnostics system is considered in two aspects: as the efficiency of design process and efficiency of result of designing, i.e. the system which is created. Design regularities of an automated pedagogical diagnostics system are determined and substantiated.
Keywords: automated system; pedagogical diagnostics